Contributions of toys and games in early childhood education - Prado , Roseli Silva Amaral; Farias, Wanerdson Santos de (Seven Editora, 2023)
Games and games have a creative, imaginary, innovative and socializing character  and therefore gain more  and more space in the school routine, especially in Early Childhood Education. Playfulness is, therefore, a means of promoting the integral development of the child, as he seeks to understand the world that surrounds him and builds his relationship with knowledge in a unique and participatory way. The present research, essentially bibliographic, aims  to investigate the contributions of play in the stage of Early Childhood Education, without losing sight of Piaget's ideas. To this end, we consulted books and scientific articles by authors who discuss the subject, such as: KIshimoto (2001), Sneyders (1996), Santos  (2006), Brougère (2010), among others. The results point to the importance of pedagogical practices involving play, from the perspective of a coherent action on the part of teachers, to fulfill their function in favor of the integral formation of the student, in view of the rights of learning. DOI:https://doi.org/10.56238/sevened2023.008-004